Heat-Aggregated Noninfectious Influenza Virus Induces a More Balanced CD8(+)-T-Lymphocyte Immunodominance Hierarchy Than Infectious Virus - Cho, Yunjung (American Society for Microbiology, 2003)
CD8(+)-T-cell (T(CD8+)) responses to infectious viruses are characterized by an immunodominance hierarchy in which the majority of T(CD8+) respond to one or a few immunodominant determinants, with a minority of T(CD8+) responding to a number of subdominant determinants. It is now well established that exogenous antigens are capable of inducing T(CD8+) to such immunodominant determinants, but the diversity of the response and the nature of the immunodominance hierarchy have not been examined. We addressed this issue by characterizing T(CD8+) responses to influenza virus preparations rendered inert by incubation for 10 min at 100°C, as first reported by Speidel et al. (Eur. J. Immunol. 27:2391-2399, 1997). Extending these findings, we show that the primary T(CD8+) response to boiled virus can be sufficiently robust to be detected ex vivo by intracellular cytokine staining and that the response encompasses many of the peptides recognized by T(CD8+) induced by infectious virus. Importantly, the immunodominance hierarchy elicited was leveled, and we were unable to detect T(CD8+) that were specific for boiled virus. We used peritoneal exudate cells as antigen-presenting cells in vitro, and a number of observations indicated that boiled virus is processed via a phagocytic route that is likely to be endosomal in nature. These findings suggest that the repertoires of immunogenic peptides generated by endosomes and cytosolic processes overlap to a surprising degree. Furthermore, they demonstrate that the form of antigen administered can influence immunodominance hierarchies and that exogenous-antigen vaccines can induce broad and balanced T(CD8+) responses.